2023
DOI: 10.1111/bjet.13302
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness, prior experience, achievement emotions and academic procrastination in online learning environments

Abstract: Academic procrastination refers to individuals' unnecessary postponement of their coursework and is harmful for academic performance. When situated in self-placed and remote learning environments, students' tendency to procrastinate increases. Therefore, understanding why students procrastinate and identifying who is more likely to delay unnecessarily in online learning environments is an important area to study. The goal of this study was to respond to this call by examining the structural relations between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The results concerning personal experiences are of course intimately linked to students' perceptions about the quality of the online education they received. Indeed, other works makes a direct link between low motivation and the feeling that online education is not as good as that delivered in traditional face-to-face settings (e.g., [79,80]). The forced nature of the COVID-19 online learning experience is also a factor cited by other authors as leading to the lack of enjoyment reported with respect to online courses (e.g., [81,82]).…”
Section: Student Adaptation To Online Educationmentioning
confidence: 99%
“…The results concerning personal experiences are of course intimately linked to students' perceptions about the quality of the online education they received. Indeed, other works makes a direct link between low motivation and the feeling that online education is not as good as that delivered in traditional face-to-face settings (e.g., [79,80]). The forced nature of the COVID-19 online learning experience is also a factor cited by other authors as leading to the lack of enjoyment reported with respect to online courses (e.g., [81,82]).…”
Section: Student Adaptation To Online Educationmentioning
confidence: 99%
“…Pekrun also classifies achievement emotions into activity-related and outcome-related emotions, which arise during learning and achievement contexts. Furthermore, Forsblom et al (2022) and Cheng, Chang et al (2023) suggest that achievement emotions can affect cognitive aspects during the learning process and are associated with the outcome of that process. Positive achievement emotions have been found to enhance effort and attention and facilitate memory recall, as observed by Meinhardt and Pekrun (2003).…”
Section: Achievement Emotionsmentioning
confidence: 99%
“…As technology continues to advance, emotions play a crucial role in e-learning. Previous studies investigated the importance of emotions in e-learning contexts (Cheng, Chang et al, 2023;Forsblom et al, 2022;Meinhardt & Pekrun, 2003;Pekrun et al, 2011). Emotions in the learning process emphasize the need to cultivate specific "emotional competencies" as a prerequisite for successful learning.…”
Section: Achievement Emotionsmentioning
confidence: 99%
See 1 more Smart Citation